2009
DOI: 10.1016/j.canlet.2009.05.030
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-138 suppresses invasion and promotes apoptosis in head and neck squamous cell carcinoma cell lines

Abstract: Metastasis is a critical event in the progression of head and neck squamous cell carcinoma (HNSCC). To identify microRNAs associated with HNSCC metastasis, 6 paired HNSCC cell lines with different metastatic potential were examined. Using microarrays, a panel of differentially expressed microRNAs was identified, including reduction of miR-138 in highly metastatic cells. Ectopic transfection of miR-138 suppressed cell invasion and led to cell cycle arrest and apoptosis. Knockdown of miR-138 enhanced cell invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
181
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(198 citation statements)
references
References 49 publications
15
181
0
2
Order By: Relevance
“…In nasopharyngeal carcinoma, miR-138 markedly decreased cell proliferation and colony formation in vitro, and tumorigenesis in vivo (37). In head and neck squamous cell carcinoma, ectopic transfection with miR-138 inhibited cell invasion, and enhanced cell-cycle arrest and apoptosis (22). The evidence from these prior studies, together with the findings of the present study, indicates that miR-138 acts as a tumor suppressor in cancer.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In nasopharyngeal carcinoma, miR-138 markedly decreased cell proliferation and colony formation in vitro, and tumorigenesis in vivo (37). In head and neck squamous cell carcinoma, ectopic transfection with miR-138 inhibited cell invasion, and enhanced cell-cycle arrest and apoptosis (22). The evidence from these prior studies, together with the findings of the present study, indicates that miR-138 acts as a tumor suppressor in cancer.…”
Section: Discussionsupporting
confidence: 76%
“…miR-138/SP1-based targeted therapy could therefore represent a promising therapeutic strategy for HCC patients. Downregulation of miR-138 has been reported in diverse types of human cancer, including anaplastic thyroid carcinoma (21), head and neck squamous cell carcinoma (22), clear cell renal cell carcinoma (23), ovarian cancer (24), glioblastoma (25), colorectal cancer (26), non-small cell lung cancer (NSCLC) (27), pancreatic cancer (28) and breast cancer (29). Furthermore, reduced miR-138 expression was associated with a number of cancer characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…miR-138 was reported to act as a tumor suppresser and serve as a therapeutic target in head and neck squamous cell carcinoma patients (43) and be involved in regulation of ABCB1 transcription (27). Therapy targeting miR-138 may be a therapeutic approach to inhibit ABCB1 in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of miR-7 in breast cancer has also been proven in the study by Kong et al (42), who demonstrated the inhibition of epithelial-to-mesenchymal transition and metastasis of breast cancer cells via targeting FAK expression. Previously studies have demonstrated that miR-7 is also downregulated in advanced tongue squamous cell carcinoma cell lines (43,44). Therefore, our current results are consistent with previous findings.…”
Section: Discussionmentioning
confidence: 98%